PELATIHAN DAN PENGEMBANGAN KARIR TERHADAP PRESTASI PESERTA BALAI PELATIHAN VOKASI DAN PRODUKTIFITAS (BPVP) PADANG KEMENTERIAN KETENAGAKERJAAN RI - Tania Alifa Sukma; Henryanto Abaharis (Jurnal Bina Bangsa Ekonomika, 2024)
This purpose of this study is to determine the influence of Training and Career Development on the Performance of Participants at the Vocational and Productivity Training Center (BPVP) in Padang, Ministry of Manpower of the Republic of Indonesia. The research method used is quantitative. Sampling was done using probability sampling, with a total of 91 respondents. The data analysis technique used is multiple linear regression. The hypothesis testing results show that training has a positive and significant effect on participant performance, and career development has a positive and significant effect on participant performance.